Real Time Image Segmentation for Face Detection Based on Fuzzy Logic - Dawwd, Shefa , A.; Mahmood, Basil Sh.; Majeed, Rasha , E. (Nahrain University College of Engineering Journal, 2008)
The segmentation of objects whose colorcomposition is not trivial represents a difficult task. In this work we propose a fuzzy algorithm application for the segmentation of such objects. It is chosen; by the characteristics that it represents the face segmentation. A priori knowledge about spectral information for certain face skin region classes is used in order to classify image in fuzzy logic classification procedure. The basic idea was to perform the classification procedure first in the supervised and then in fuzzy logic manner. Some information, needed for membership function definition, was taken from supervised maximum likelihood classification. The system uses three membership functions which are taken as Gaussian distribution curve. For real time needs, the system is implemented on an FPGA.